Understanding the audiological care of patients with co-existing dementia or mild cognitive impairment and hearing loss in the United Kingdom National Health Service: A qualitative study - Sian Calvert; Aaron Chitty; Alex Langdon; Emma Broome; Helen Henshaw; Sarah Somerset; Tom Dening; Eithne Heffernan (PLoS ONE, 2025)
Background Hearing loss is common among people living with dementia and can exacerbate the symptoms associated with dementia. The effective management of hearing loss can positively impact quality of life and help alleviate dementia-related symptoms. Little is known about current audiological pathways in the National Health Service (NHS) for adults living with dementia or mild cognitive impairment. Objectives To understand the current NHS audiological care pathways for adults living with dementia or mild cognitive impairment. Design Qualitative study Results Thirty-three NHS audiologists in the United Kingdom (UK) completed a qualitative survey about current adult audiological care pathways for people living with dementia or mild cognitive impairment, and 14 of those also participated in a follow-up interview. Data from the surveys and interviews were combined and analysed using reflexive thematic analysis. The key findings included the importance of person-centred care, the active involvement of carers, and the need for tailored approaches, including using adapted and additional tests to assess hearing loss while offering a variety of hearing interventions. Audiologists expressed a desire for more service integration, such as domiciliary visits, and emphasised the importance of adapting environments and practices, such as dementia-friendly spaces and routine dementia education for staff, to better support individuals living with these co-existing conditions, Conclusions These findings can help inform the development of formal clinical practice guidelines and evidence-based training to support audiological care for people living with dementia and mild cognitive impairment in the United Kingdom.